Problem-based learning: a proposal for teacher qualification - Hernández, Rubinsten; Moreno, Sandra Maritza (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This text describes a research experience of qualification with natural science teachers,which had the objective of them adopting a strategy of educational work and thus considering alternatives that would favour the development of competences, of critical thinking, and of school scientific knowledge construction; as well as recognizing the value of team work to favour the learning development. The proposal reflects the experience, considerations and suggestions gained during two years of implementation. It was developed based on a staged structure and considered the coherence between the conceptual elements of the problem-based learning strategy and its implementation. The strategy is based on existing documentation in the area but adjusted to the specific context of development. The results revealed the potential of the strategy. The cooperative work, the structuring concepts, and the metacognitive process, among other aspects, are highlighted; but, at the same time, their limitations are recognized regarding the time required for the design of the problem and the implementation of the strategy.